Neurologic Complication Due to Crystallization After Drug Interaction Between Alkalized Lidocaine and Ropivacaine: A Case Report and in vitro Study - Zhu, Afang; Pei, Lijian; Liu, Wei; Cheng, Wencong; Zhang, Yu; Huang, Yuguang (Frontiers in Medicine, 2022)
Background: For pregnant women transferred to emergency caesarean section after receiving epidural labor analgesia, there is still a debate over the effective and safe means of rapidly delivering surgical anaesthesia. Alkalized lidocaine is often adopted for fast onset time; however, crystallization of the anaesthetic in the epidural space can cause severe neurologic symptoms. Case Presentation: We report a case of a pregnant woman who underwent emergency caesarean section with satisfied analgesia but experienced severe weakness and paranaesthesia in the lower limb. After excluding lumbar disc herniation, obstetric nerve injury, and anaesthesia technique causes by symptoms signs and magnetic resonance imaging, drug-related injury became the most likely cause. Our in vitro testing confirmed the obvious precipitation of additional anaesthetic-concentrated ropivacaine (0.5% to 1%) with pretreated alkalized lidocaine. With trophic neurotherapy, the parturient attained prompt relief of weakness by day four, but delayed recovery of numbness, which lasted for four weeks. Conclusion: To date, this may be the first case reporting drug crystallization in epidural space. Our study confirmed the rapid onset of alkalized lidocaine and its safety to pretreated routine labor dose of ropivacaine (0.09%). However, additional anaesthetic-concentrated ropivacaine (0.5% to 1%) to maintain the anaesthesia and analgesia level is not suggested.